Noise characterization and exposure at a ski resort - Radman, Audra, author; Sandfort, Delvin, advisor; Brazile, William, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2012)
This study examined the noise exposures of employees at a ski resort working in the job categories of snowmaker, snow groomer, or chair lift operator. Noise exposures for all employees were obtained using personal noise dosimetry. Snowmakers were monitored during their normal 12-hour work shifts (n=19 for both night and day shifts) and results indicated that 70% of the snowmakers exceeded the OSHA 12-hour AL (82 dBA), 32% exceeded the OSHA recommended 12-hour PEL (87 dBA), 11% exceeded the OSHA PEL (90 dBA), and 63% exceeded the ACGIH® 12-hour TLV® (83 dBA). When comparing noise exposures of the day-shift snowmaker crew to the night-shift crew, results indicated that 100% of the night-shift crew exceeded the OSHA 12-hour Action level (82 dBA), 40% exceeded the OSHA recommended 12-hour PEL (87 dBA), 10% exceeded the OSHA PEL (90 dBA), and 100% exceeded the ACGIH® 12-hour TLV® (83 dBA). Results also indicated that of the day-shift snowmaker crew, 33% exceeded the OSHA 12-hour AL (82 dBA), 22% exceeded the OSHA recommended 12-hour PEL (87dBA), 11% exceeded the OSHA PEL (90 dBA), and 44% exceeded the ACGIH® 12-hour TLV® (83 dBA). Snowmaker equipment was also analyzed using a sound level meter for eight different snowmaking machines, with results revealing a range of 83 dBA to 116 dBA. The chair lift operation population (n=20) was monitored for work shifts varying from 8 to 10 hours. The findings indicated that 5% exceeded the OSHA 10-hour AL (83 dBA), none of the chair lift worker population exceeded the OSHA recommended 10-hour PEL (88 dBA), none exceeded the OSHA PEL (90 dBA), and 10% exceeded the ACGIH® 10-hour TLV® (84 dBA). Chair lift equipment was also analyzed using a sound level meter, which indicated a range of 75 dBA to 81 dBA. Noise exposures for snow groomers were ascertained for entire 10-hour work shifts (n=19). The results from this study indicated that none of the snow groomers exceeded any published occupational noise criteria from OSHA or ACGIH®. Snow grooming machines were also characterized using a sound level meter for four different snow grooming machines, which illustrated a range of 74 dBA to 78 dBA. It is recommended that management take steps in order to reduce the exposure times to excessive noise for snowmaker employees, either by obtaining snowmaking machines that generate noise at a safe level or by decreasing work shifts of snowmaker employees. It is also recommended that snowmaker employees continue to wear and maintain their current hearing protection devices. It is recommended that this ski resort continue the participation of all snowmaker employees in the current hearing conservation program. Further research is also recommended in order to determine if chair lift operator employees should be enrolled into a hearing conservation program to help ensure that no employees are at risk of sustaining hearing damage.
Keywords: noise exposure; ski resort